Assessment of Users' Needs and Expectations Toward Clinical Practice Guidelines to Support the Rehabilitation of Adults With Moderate to Severe Traumatic Brain Injury. Issue 5 (September 2018) - Lamontagne, Marie-Eve; Bayley, Mark Theodore; Marshall, Shawn; Kua, Ailene; Marier-Deschênes, Pascale; Allaire, Anne-Sophie; Schmouth, Marie-Eve; Kagan, Corinne; Truchon, Catherine; Swaine, Bonnie
Abstract : Objective: Stakeholder engagement in clinical practice guideline (CPG) creation is thought to increase relevance of CPGs and facilitate their implementation. The objectives were to survey stakeholders involved in the care of adults with traumatic brain injury (TBI) regarding general perceptions of CPGs, key elements to be included, and needs and expectations about format and implementation strategy. Settings: Hospitals and inpatient and outpatient rehabilitation facilities providing services to persons with TBI. Participants: Stakeholders identified as primary end users of the CPG: clinicians, hospital leaders, health system managers, and funders in Quebec and Ontario (Canada). Design: Cross-sectional online survey conducted between May and September 2014. Results: In total, 332 individuals expressed their needs and expectations. Despite positive perceptions of CPGs, only a small proportion of respondents used them. Intensity and frequency of interventions, behaviors disorders and cognitive function impairment, and social participation and community life were important subjects to cover in the CPG. Finally, respondents asked for specific recommendations including a ranking of recommendations based on level of underlying evidence. Conclusion: Respondents have important expectations toward a CPG. We anticipate that early and meaningful engagement of end users could facilitate CPG implementation.